2017
DOI: 10.1126/sciadv.1700342
|View full text |Cite|
|
Sign up to set email alerts
|

High thermal conductivity in electrostatically engineered amorphous polymers

Abstract: High thermal conductivity in amorphous polymer films via ionization-induced chain extension and stiffening, and dense packing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
92
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(104 citation statements)
references
References 59 publications
10
92
2
Order By: Relevance
“…This finding is inconsistent with the proposed mechanism to explain the enhanced thermal conductivity of PAA when ionization increases, 11 which hypothesized that the Coulombic repulsion of the ionized monomers straightens the chains and thus increases heat transfer along the chain backbone. 11 We believe that the increasing thermal conductivity of ionized PAA is not due to the polymer chain stretching. While we can not claim that our in silico chain conformation is the same as that in experiments, 11 by strengthen the PANa backbone we can increase the R g from 12.3 to 16.1 Å in the model, but the thermal conductivity merely increases from ~ 0.67 to ~ 0.70 W/m.K.…”
Section: The Molecular Conformation Has No Effect On Thermal Conductimentioning
confidence: 68%
See 1 more Smart Citation
“…This finding is inconsistent with the proposed mechanism to explain the enhanced thermal conductivity of PAA when ionization increases, 11 which hypothesized that the Coulombic repulsion of the ionized monomers straightens the chains and thus increases heat transfer along the chain backbone. 11 We believe that the increasing thermal conductivity of ionized PAA is not due to the polymer chain stretching. While we can not claim that our in silico chain conformation is the same as that in experiments, 11 by strengthen the PANa backbone we can increase the R g from 12.3 to 16.1 Å in the model, but the thermal conductivity merely increases from ~ 0.67 to ~ 0.70 W/m.K.…”
Section: The Molecular Conformation Has No Effect On Thermal Conductimentioning
confidence: 68%
“…[ 11 ]. In this range, our predicted thermal conductivity is 0.45-0.59 W/m.K, with the lower bound agreeing exactly with the measured data from Ref.…”
Section: The Thermal Conductivity Comparison Between Our Model and Exmentioning
confidence: 80%
“…Therefore, to know if F ll 0 l 00 can assume values different than zero, it is enough to check if the direct product of the irreducible representations of e l , e l 0 and e l 00 contains the totally symmetric representation. In other words, given the irreducible representations G el , G e l 0 and G e l 00 , for which the eigenvectors e l , e l 0 , e l 00 are respectively a basis, then F ll 0 l 00 s00G e l 5G e l 0 5G e l 00 4A (8) which states that if the direct product among the irreducible representations contain the totally symmetric representation A, then the l + l 0 ¼ l 00 scattering is allowed. The magnitude of the allowed process depends on the actual numerical value of the interaction strength which, in turn, depends on the specic values of the anharmonic force constants.…”
Section: Methodsmentioning
confidence: 99%
“…Deviations are attributed to anharmonic terms in the interatomic displacements, which allow for phonon-phonon recombination processes. The ne tuning of such processes would allow selective and powerful control of a vast variety of phenomena such as spin relaxation, 3,4 protein dynamics, 5 thermoelectricity, 6 phase transition, 7 and thermal conductivity 8 among others, which are the basis of the design of ordinary and metamaterials. 9 In this work, we show how it is possible to state if a multiphonon scattering process is allowed by means of symmetry arguments only, without the need to compute the actual value of the interaction strength.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] A number of recent studies have revealed that polymer thermal conductivity is strongly related to its molecular level conformation. 6,8,[10][11][12][13][14] For example, stiffer molecular backbones can make the chains straighter even in the amorphous state 15 and thus increase the amount of heat that can be transferred through the strong backbone. 12 In polymer blends, it is reported that increasing the inter-chain interaction through engineering hydrogen bonds can stretch the polymer chains and enhance the thermal conductivity up to 1.5 W/(m.K).…”
Section: Introductionmentioning
confidence: 99%